LSD1 is a targetable vulnerability in gastric cancer harboring TP53 frameshift mutations - Suzeng Wang; Chunyu Yang; Junhui Tang; Kaiqing Wang; Hao Cheng; Surui Yao; Zhaohui Huang; Bojian Fei (Clinical Epigenetics)
Abstract Background TP53 mutations are linked to aggressive progression and chemoresistance in gastric cancer (GC). Frameshift mutation is the second most common mutation type of TP53. However, the consequences of this mutation type in GC were not well understood, and targeted therapies for cancer patients harboring frameshift mutations were also not established. Histone methylation significantly influences tumorigenesis in TP53-mutated cancers, and related inhibitors are emerging as specific therapeutic strategies. Methods and results By treating GC cell lines harboring various TP53 mutation types with a library of histone demethylase inhibitors, we identified that GSK690, a reversible inhibitor of lysine-specific demethylase 1 (LSD1), selectively inhibits GC cells harboring TP53 frameshift mutations without nuclear localization sequence (NLS) (termed TP53 Frameshift NLS), which accounts for 89% TP53 frameshift mutations in GC patients. GSK690 showed significant specific inhibition in vitro and in vivo against this subtype by inducing G1/S cell cycle arrest via the LSD1-CCNA2 axis. Importantly, dual-luciferase assays and ChIP-qPCR confirmed that the loss of transcriptional repression activities of p53 in drives LSD1 upregulation in TP53 Frameshift NLS cancer cells. Conclusions In summary, our results indicate that the nuclear localization deficiency of p53 accounts for increased expression of LSD1 in TP53 Frameshift NLS GCs. GSK690 inhibits cell cycle progression and tumor growth by suppressing aberrantly activated LSD1-CCNA2 signaling in this GC subtype, counteracting malignant proliferation and thereby providing a precise therapeutic strategy for GC patients with TP53 Frameshift NLS.